2013
DOI: 10.1155/2013/385219
|View full text |Cite
|
Sign up to set email alerts
|

Anthricin Isolated fromAnthriscus sylvestris(L.) Hoffm. Inhibits the Growth of Breast Cancer Cells by Inhibiting Akt/mTOR Signaling, and Its Apoptotic Effects Are Enhanced by Autophagy Inhibition

Abstract: Anthricin (deoxypodophyllotoxin) is a natural product isolated from Anthriscus sylvestris (L.) Hoffm. (Apiaceae). Here, we investigated the effect of anthricin on autophagy and mammalian target of rapamycin (mTOR) signaling as anticancer actions in breast cancer cells. Many studies have supported the contention that the phosphoinositide 3-kinase (PI3K)/Akt/mTORC1 pathway is considerably deregulated in breast cancer and that autophagy plays important roles in the development of this type of cancer, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
(40 reference statements)
1
27
0
1
Order By: Relevance
“…Recent reports have suggested that the Akt‐mTOR signaling pathway is a major negative regulator of autophagy . The suppression of mTOR activity by rapamycin can induce autophagy and also reduce cell growth in different cancer cells . Now, we further determined whether the Akt‐mTOR pathway is involved in AMP‐induced autophagy.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Recent reports have suggested that the Akt‐mTOR signaling pathway is a major negative regulator of autophagy . The suppression of mTOR activity by rapamycin can induce autophagy and also reduce cell growth in different cancer cells . Now, we further determined whether the Akt‐mTOR pathway is involved in AMP‐induced autophagy.…”
Section: Resultsmentioning
confidence: 89%
“…Autophagy has often been observed as a consequence of ER stress and regarded as an alternate pathway to relieve ER stress or take part in cell death induced by ER stress . Activation of ER stress has recently been found in a variety of chemotherapeutic candidates' treatment in cancer cells along with induction of autophagy, although the mechanistic link between autophagy and ER stress remains not exactly clarified . Our previous study has shown that AMP could activate ER stress in both MCF‐7 and MDA‐MB‐231 cells, and PERK‐CHOP pathway plays a vital role in AMP‐induced cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). In particular, in this cell line treatment with either bafilomycin A1, 3‐methyladenine or chloroquine, which are down‐regulators of autophagy, resulted in the potentiation of apoptosis induction following exposure to diverse compounds of natural origin such as plant‐derived anthricin, apigenin and sulforaphane …”
Section: Discussionmentioning
confidence: 92%